2017
DOI: 10.15560/13.3.2108
|View full text |Cite
|
Sign up to set email alerts
|

New records and update on the geographic distribution of Lontra longicaudis (Olfers, 1818) (Carnivora: Mustelidae) in Seasonally Dry Tropical Forests of northeastern Brazil

Abstract: We confirmed occurrences of Lontra longicaudis (Olfers, 1818) in Seasonally Dry Tropical Forests (Caatinga) of 10 river basins in northeastern Brazil, reporting the first records of the species in five of them. The species was not found in river basins totally inserted in Caatinga, nor where Caatinga borders Cerrado (Piauí state), indicating a gap in the species distribution. We report the first otter occurrence in Piauí, in the Cerrado biome of the southern part of the state. The relevance of these results fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
3
0
4
Order By: Relevance
“…Nineteen new records of L. longicaudis were obtained in the municipalities along the eastern coast of Rio Grande do Norte and confirm the results of Laurentino and Sousa (2014) and Rosas-Ribeiro et al (2017) who found this species in 15 municipalities. We confirmed the occurrence records of L. longicaudis in all eight river basins studied.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Nineteen new records of L. longicaudis were obtained in the municipalities along the eastern coast of Rio Grande do Norte and confirm the results of Laurentino and Sousa (2014) and Rosas-Ribeiro et al (2017) who found this species in 15 municipalities. We confirmed the occurrence records of L. longicaudis in all eight river basins studied.…”
Section: Resultssupporting
confidence: 80%
“…The first record of the species was by Laurentino and Sousa (2014) in the municipalities of Baia Formosa, Canguaretama, Ceará-Mirim, Extremoz, Macaíba, Nísia Floresta, Parnamirim, Pedro Velho, Senador Georgino Avelino, and Vila Flor. Rosas-Ribeiro et al (2017) later updated the records in the Brazilian Northeast Region and confirmed the presence of L. longicaudis in Rio Grande do Norte in the municipalities of Macaíba, São José de Mipibu, Passagem, Santo Antônio, São José do Campestre, and Montanhas.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As informações sobre a ocorrência de L. longicaudis ainda se apresentam de forma incipiente no estado de Pernambuco, com relatos nas últimas décadas (Rosa-Ribeiro;Ranulpho & Venticinque, 2017). Os registros obtidos neste trabalho reforçam as constatações acerca da presença desse mustelídeo e refutam o entendimento de que a espécie havia sido extinta do estado, conforme sugerido por Pontes, Beltrão e Santos (2019).…”
Section: Discussionunclassified
“…Biodiversity conservation strategies at a local scale should be designed, based on an understanding of the occurrence and distribution of species ( Tobler et al 2008 ) and the impacts of human activities on vulnerable species ( Tobler et al 2008 , Cheyne et al 2016 , Rosas-Ribeiro et al 2017 ). Thus, in this study, we present the results of a survey of medium- and large-sized terrestrial mammals from two Atlantic Forest remnants of the Municipality of Conceição dos Ouros in the State of Minas Gerais, southeast Brazil.…”
Section: Introductionmentioning
confidence: 99%